Modular integrated SiC MOSFET matrix converter - Aliyu, Attahir Murtala; Castellazzi, Alberto; Lasserre, Philippe; Delmonte, N. (2017)
This paper presents the assembly and characterization of an integrated all SiC 3-to-1 phases matrix converter, of typical application in domains requiring harsh environment withstand capability with high reliability and availability levels (e.g., renewable energies, solid-state transformation, smart grids, electric transport). Commercially available silicon-carbide (SiC) power MOSFETs are procured in bare-die form to develop custom-packaged bi-directional switches, with an advanced approach aiming to optimize the electro-thermal and electro-magnetic performance at switch level. Advanced cooling and packaging solutions at system level enable modularity with reduced impact of single component failure on the overall system, contributing to significantly reduced maintenance and repair costs.